A honokiol-enriched Magnolia officinalis Rehder & E.H. Wilson. bark extract possesses anxiolytic-like activity with neuroprotective effect through the modulation of CB1 receptor. (5th May 2021) - Borgonetti, Vittoria; Governa, Paolo; Manetti, Fabrizio; Miraldi, Elisabetta; Biagi, Marco; Galeotti, Nicoletta
Abstract: Objectives: The exposure of neurons to an excessive excitatory stimulation induces the alteration of the normal neuronal function. Mood disorders are among the first signs of alterations in the central nervous system function. Magnolia officinalis bark extract has been extensively used in the traditional medicine systems of several countries, showing several pharmacological activities. Honokiol, the main constituent of M . officinalis, is a GABA modulator and a CB1 agonist, which is deeply investigated for its role in modulating mood disorders. Methods: Thus, we evaluated the possible neuroprotective effect of a standardized M. officinalis bark extract (MOE), enriched in honokiol, and its effect on animal mood behavioural tests and in an in vitro model of excitotoxicity. Key findings: MOE showed neuroprotective effect using SH-SY5Y cells, by normalizing brain-derived neurotrophic factor release. Then, we tested the effect of MOE in different behavioural tests evaluating anxiety and depression and we observed a selective anxiolytic-like effect. Finally, we confirmed the involvement of CB1 in the final effect of MOE by the co-administration of the CB1 antagonist, AM251. Conclusion: These results suggest that MOE could be considered an effective and safe anxiolytic candidate with neuroprotective activity.